Community perceptions of climate change and its impact on natural resources in Umlazi and surrounding areas: A cross-sectional case study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Climate change is increasingly affecting vulnerable communities in South Africa, particularly those reliant on natural resources. Umlazi and the surrounding areas face challenges such as flooding, water scarcity, and biodiversity loss. Understanding community perceptions is essential for developing effective adaptation strategies and resource management plans. Methods A cross-sectional mixed-methods case study design was used. Quantitative data were collected via structured questionnaires administered to 120 residents of Umlazi and neighbouring communities. Qualitative data were gathered through focus group discussions with community leaders, youth, and environmental activists. Quantitative data were analysed using descriptive statistics; qualitative data were thematically analysed. Results Of the 120 participants, 65 (54%) were female and 55 (46%) male, aged 18 to 65 years (mean age = 34.8 years). The majority (72%) had resided in Umlazi for more than 10 years. Quantitative findings showed that 82% of respondents observed significant climate changes over the past decade, with erratic rainfall (79%) and rising temperatures (68%) most frequently reported. Over 70% linked these changes to declining water quality, reduced agricultural yields, and biodiversity loss. Qualitative findings revealed three major themes: (1) Limited access to climate information: “We do not receive proper education on climate risks or what to do when disasters happen” (community leader); (2) Concerns over weak institutional response: “Local government promises support but we don’t see it on the ground” (youth representative); and (3) Desire for greater community involvement: “We want to form local committees to protect our resources” (environmental activist). Conclusion Communities in Umlazi are aware of climate change impacts but face constraints in adaptive capacity due to limited information, infrastructure gaps, and weak institutional support. Recommendation Localized climate education, sustainable resource management, and community-led adaptation initiatives should be prioritized through partnerships between universities, local government, and civil society.